Is frequency speed of kick test responsive to training? A study with taekwondo athletes - da Silva Santos, J. F.; Franchini, E. (Sport Sciences for Health, 2016)
The purpose of this study was to investigate the frequency speed of kick test (FSKT) responsiveness to 9 weeks of taekwondo-specific training. Eight black-belt taekwondo athletes (mean and standard deviation; body mass: 74 ± 15 kg; height: 178 ± 9 cm; age: 24 ± 4 years; practice time: 12 ± 6 years), volunteered to participate. Each athlete performed the 10 s version of the test (FSKT10s) and five sets of 10 s with 10 s intervals (FSKTmult) pre and post 9 weeks of taekwondo training. There were increased (p < 0.05) performance in the FSKT10s (number kicks pre vs post: 20 ± 1 vs 21 ± 2) and in the FSKTmult variables (number kicks pre vs post: FSKT1: 20 ± 1 vs 23 ± 2; FSKT2: 19 ± 2 vs 22 ± 2; FSKT3: 18 ± 2 vs 21 ± 2; FSKT4: 17 ± 2 vs 21 ± 2; FSKT5: 17 ± 2 vs 20 ± 2; FSKTtotal: 90 ± 9 vs 107 ± 10). In conclusion, FSKT is responsive and sensible to short-term taekwondo training and can be applied by coaches to monitor sport-specific performance.